3D motion analysis system for analyzing recurve archery technique: a pilot study - Aziz, Puteri Salamah Abdul
The purpose of the study is to evaluate 3D motion analysis system for analyzing recurve archery technique. The subject is highly-skilled archer (Kelantan state archer) who volunteered to participate in this study. Pre and post-test score consisted of the total points for six arrows shot at ten feet were collected.3D motion analysis (Qualysis) system was used to record the technique of the archers (stance, posture and aiming) and it was measured simultaneously. After practicing for several minutes to accustom to the markers and testing environment, the subject was asked to shoot 12 arrows where six with their own techniques and another six with modified techniques according to Kirsik Lee books — Total Archery. The technique of recurve archery was further divided into 11 steps for analyzing purposes. Wilcoxon signed rank test was used to detect the difference between elite’s technique and suggested technique based on 3D motion analysis data. The results of using Wilcoxon sign rank test proves that there is significance difference of eight steps which are stance that should be approximately shoulder width apart, 30 degree stance open to the target, 60/40 ratio of weight on the balls and heels of the feet, the toes should point roughly parallel, the legs must be straight but not locked, the head sits out over the chest and drawing elbow torque show significance difference where p (<-05) = .028. Another 3 steps showed no significance difference, which are the posture where hips must be tucked forward to create a flat back p (<.05) = .916, shoulder alignment must point well past the line of the arrow (to the right of the target) p (<.O5) = .173, and the front shoulder should push forward the target as far as possible p (<.05) = .600. From the result it showed that 3D motion analysis system can be used and reliable in detecting the difference of archery technique. It can be used in measuring and analyzing archery technique in the future.